2012
DOI: 10.1108/17468801211209938
|View full text |Cite
|
Sign up to set email alerts
|

A first look at the properties of India's volatility index

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
2
25
0
4
Order By: Relevance
“…The assumption of leverage is affirmed. Kumar (2012) found that changes in the implied volatility index Ivix are negatively correlated to the returns of the Nifty 225 market index of the Indian stock market. Furthermore, he showed that during extreme stock market movements, this relationship becomes insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The assumption of leverage is affirmed. Kumar (2012) found that changes in the implied volatility index Ivix are negatively correlated to the returns of the Nifty 225 market index of the Indian stock market. Furthermore, he showed that during extreme stock market movements, this relationship becomes insignificant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kumar (2012) finds negative association between the India VIX and stock market returns and the presence of leverage effect significantly around the middle of the joint distribution. Bagchi (2012) constructs value-weighted portfolios based on beta, market-to-book value and market capitalisation parameters, and reports a positive and significant relationship between the India VIX and the returns of the portfolios.…”
Section: Review Of Literaturementioning
confidence: 88%
“…In the Indian context, Kumar (2012) and Bagchi (2012) studied the India VIX and its relationship with the Indian stock market returns. Kumar (2012) finds negative association between the India VIX and stock market returns and the presence of leverage effect significantly around the middle of the joint distribution.…”
Section: Review Of Literaturementioning
confidence: 99%
“…7 Elsewhere, lack of the asymmetry in association between implied volatility and stock returns was reported for Canadian (Siriopoulos and Fassas, 2008) and Australian indices (Frijns et al, 2010;Dowling and Muthuswamy, 2005). Strong asymmetric association was reported for Korean (Ting, 2007) and Indian (Kumar, 2012) indices. We start the analysis by regressing daily returns of all sample stock indices on the corresponding volatility index returns:…”
Section: Association Of Returns and Implied Volatilitymentioning
confidence: 99%